Executive Committee Minutes 2019-04-11 - Academic Senate:::::::::
Agenda Approved. Minutes of 3/28/19 Approved. Chair Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Associated Students Report. From EPC: Revision to the GE Curriculum – Approved as a business item for the Senate. Proposed By-Law Change - Name change of Faculty Subcommittee on Sponsored Programs (FSSP) to Faculty Subcommittee on Scholarly Activities (FSSA) – Approved as a business item for the Senate. From S&F: Carryover Business – referred back to S&F. Academic Advising Task Force Report – Approved for endorsement as business for the Senate. APARC Report. FSAC Report. SAC Report. Rep to SEC Report. Statewide Senator Report. Senate Agenda approved.